2009
DOI: 10.26719/2009.15.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Injury epidemiology in Kermanshah: the National Trauma Project in Islamic Republic of Iran

Abstract: In a cross-sectional study, all trauma patients hospitalized for 24 hours or more over a 4-month period in Taleghani hospital, the only referral teaching centre in Kermanshah city, were studied (n = 779). Mean age was 34.7 (standard deviation 19.9) years. Male, unemployed and illiterate patients predominated. Road traffic accidents, falls and interpersonal violence were the most common mechanisms of injury. Among road traffic accident victims, pedestrians were the most vulnerable group. A total of 7.8% of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…1 About 20% of referral to emergency departments was for the hand and wrist problems. 2 According to an Injury epidemiology of the National Trauma Project in Iran, hand and wrist injuries were accounted for 5.4%. 2 To report patient's perception of the outcome, self-reported clinical questionnaires have been designed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 About 20% of referral to emergency departments was for the hand and wrist problems. 2 According to an Injury epidemiology of the National Trauma Project in Iran, hand and wrist injuries were accounted for 5.4%. 2 To report patient's perception of the outcome, self-reported clinical questionnaires have been designed.…”
Section: Introductionmentioning
confidence: 99%
“…2 According to an Injury epidemiology of the National Trauma Project in Iran, hand and wrist injuries were accounted for 5.4%. 2 To report patient's perception of the outcome, self-reported clinical questionnaires have been designed. Michigan Hand Outcomes Questionnaire (MHOQ) is a hand-specific patientreported questionnaire representing outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[2,10] Furthermore, it is higher than that observed in some of the neighboring countries with a similar socioeconomic pattern. [11] Messahel et al [12] reported a ratio of 6.3:1 in Saudi Arabia. This can be explained by the demographic distribution of the Abu Dhabi Emirate, as females represent only one-third of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies in Iran showed that about one-fourth of the patients with trauma had head and neck injuries and this comprised 33% to 46% of all such patients (2)(3)(4). Head and neck injuries have the highest mortality and morbidity rate among all patients with trauma (2,3,5).…”
Section: Introductionmentioning
confidence: 99%